Bottom-Stirring In An Electric-Arc Furnace: Performance Results At Iscor Vereeniging Works - M. J. U. T. Van Wijngaarden; A. T. Pieterse (The Southern African Institute of Mining and Metallurgy, 1994)
An account is given of the performance of a 37 MVA electric-arc .furnace in which bottom stirring with inert gas by an indirect-contact stirring-plug system was applied. The system, which was developed and patented by Thyssen-Stahl AG, and which is the first inert gas stirring system to be installed in South Africa, was commissioned in January 1992. Initial problems were experienced due to the blockage of stirring plugs by molten steel. The causes of these malfunctions are examined, and an account is given of how they were overcome. The system is described and evaluated. A comparison with direct-contact stirring systems shows why Iscor Vereeniging Works considered it to be more suitable for their Vaal Melt Shop. The results show that, through the successful application qf this technology, Iscor Vereeniging Works has achieved an annual cost saving of more than R2,5 million.